Our global families : Christians embracing common identity in a changing world - Johnson, Todd M. (Todd Michael), 1958- (Grand Rapids, Michigan : Baker Academic, 2015)
As Christians, we belong to not only a diverse global Christian family but also a diverse human family. Todd Johnson, a noted expert on global Christianity and world missions trends, and Cindy Wu show how divisions within these families work against our desire to bring about positive change in the world. They provide an overview of global Christian identity, exploring how we can be faithful to our own tradition while engaging Christians across denominations and be better informed as we work with people of other religions. The book utilizes the latest research data on global Christianity and world religions and includes tables, graphs, charts, and end-of-chapter discussion questions.
Our global families -- Our changing world -- Meet your global Christian family -- Meet your global human family -- It's a small world, after all -- Our changing identity -- We are family -- We are global -- We are local -- Our changing relationships -- Solidarity with Christians -- Solidarity with others -- Love thy neighbor -- Changing our world -- What we can't do -- What we can do.
Includes bibliographical references and index.
Keywords: Christianity -- 21st century; Globalization -- Religious aspects -- Christianity; Identification (Religion); Christianity and other religions; Interpersonal relations -- Religious aspects -- Christianity; Christianity; Christianity and other religions; Globalization -- Religious aspects -- Christianity; Identification (Religion); Interpersonal relations -- Religious aspects -- Christianity; 2000 - 2099